2018
DOI: 10.1530/erc-17-0507
|View full text |Cite
|
Sign up to set email alerts
|

Open issues on G3 neuroendocrine neoplasms: back to the future

Abstract: The recent recognition that grade 3 (G3) neuroendocrine neoplasms (NENs) can be divided into two different categories according to the histopathological differentiation, that is G3 neuroendocrine tumors (NETs) and G3 neuroendocrine carcinomas (NECs) has generated a lot of interest concerning not only the diagnosis, but also the differential management of such new group of NENs. However, several issues need to be fully clarified in order to put G3 NETs and G3 NECs in the right place. The aim of this review is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 60 publications
(83 reference statements)
0
6
0
1
Order By: Relevance
“…Zatelli et al [11] and Fazio and Milione [12] suggested a new classification of HG NETs, based on Ki-67 index more or less than 55%.…”
Section: Introductionmentioning
confidence: 99%
“…Zatelli et al [11] and Fazio and Milione [12] suggested a new classification of HG NETs, based on Ki-67 index more or less than 55%.…”
Section: Introductionmentioning
confidence: 99%
“…The latest group of NENs includes very heterogeneous neoplasms. Within the same histological grade, morphological features characterising these tumours are not uniform in all sites (Zatelli et al 2018). Thus, the WHO classification of 2019 distinguishes between well-differentiated G3 NETs with a mitotic count >20/2 mm 2 and/or a Ki-67 >20% and poorly differentiated NECs also with a mitotic count >20/2 mm 2 and/or a Ki-67 >20% (Nagtegaal et al 2020).…”
Section: Pathologymentioning
confidence: 99%
“…In der ENETS Consensus Guideline Update für das Management von Patienten mit funktionellen panNET und nichtfunktionellen panNET wird die PRRT bei fortgeschrittenen NET und Versagen einer medikamentösen Therapie empfohlen [25] Circa 5 % der NEN zeigen eine G3-Differenzierung mit einem OS von 41 bis 55 Monaten [94]. Bei lokalisiertem oder regional begrenztem GEP-NET G3 und NEC wird ein operatives Vorgehen angestrebt, ggf.…”
Section: Knochenmarkreserve Des Patienten Ausreichend Hoch Seinunclassified